2022
DOI: 10.1186/s12866-022-02439-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Antimicrobial and anti-biofilm potencies of dermcidin-derived peptide DCD-1L against Acinetobacter baumannii: an in vivo wound healing model

Abstract: Background The global emergence of Acinetobacter baumannii resistance to most conventional antibiotics presents a major therapeutic challenge and necessitates the discovery of new antibacterial agents. The purpose of this study was to investigate in vitro and in vivo anti-biofilm potency of dermcidin-1L (DCD-1L) against extensively drug-resistant (XDR)-, pandrug-resistant (PDR)-, and ATCC19606-A. baumannii. Methods After determination of minimum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Biofilm formation is one of the pivotal virulence factors and resistance enhancers in A. baumannii [ 65 , 66 ]. Hence, it has become imperative to develop entities with antibiofilm activities [ 67 ]. In our previously published work [ 68 ], we investigated the antibiofilm activities of cinnamic and gallic acids at ¼MIC and ½MIC concentrations, and results showed that gallic acid had a superlative antibiofilm effect against strong, biofilm-forming A. baumannii isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation is one of the pivotal virulence factors and resistance enhancers in A. baumannii [ 65 , 66 ]. Hence, it has become imperative to develop entities with antibiofilm activities [ 67 ]. In our previously published work [ 68 ], we investigated the antibiofilm activities of cinnamic and gallic acids at ¼MIC and ½MIC concentrations, and results showed that gallic acid had a superlative antibiofilm effect against strong, biofilm-forming A. baumannii isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, this problem has continued to increase and evolve [ 44 ]. Currently, antibiotic resistance is highly spreading among A. baumannii , and this is a therapeutic challenge that should be addressed and considered [ 12 ]. Herein, we found that 77.78% of A. baumannii isolates were multidrug-resistant.…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter baumannii is already one of the most common opportunistic pathogenic bacteria in clinical settings. Unfortunately, these bacteria acquire many resistance genes to many antibiotics, increasing the bacteria’s ability to survive and spread [ 12 ]. In addition, the virulence factors of these bacteria, especially their ability to form a biofilm, are an important characteristic of A. baumannii that allows them to escape the immune system and harsh environments [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This model was selected based on the known information that wound infections are one of the most significant infections caused by A. baumannii [ 79 ]. Several studies have shown the applicability of topically applied non-antibiotic agents in the treatment of A. baumannii wound infections [ 32 , 80 , 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%